CFH and CFHR Copy Number Variations in C3 Glomerulopathy and Immune Complex-Mediated Membranoproliferative Glomerulonephritis - Piras, Rossella; Breno, Matteo; Valoti, Elisabetta; Alberti, Marta; Iatropoulos, Paraskevas; Mele, Caterina; Bresin, Elena; Donadelli, Roberta; Cuccarolo, Paola; Smith, Richard J. H.; Benigni, Ariela; Remuzzi, Giuseppe; et al. (Frontiers in Genetics, 2021)
C3 Glomerulopathy (C3G) and Immune Complex-Mediated Membranoproliferative glomerulonephritis (IC-MPGN) are rare diseases characterised by glomerular deposition of C3 caused by dysregulation of the alternative pathway (AP) of complement. In approximately 20% of affected patients, dysregulation is driven by pathogenic variants in the two components of the AP C3 convertase, complement C3 (C3) and Factor B (CFB), or in complement Factor H (CFH) and Factor I (CFI), two genes that encode complement regulators. Copy number variations (CNVs) involving the CFH-related genes (CFHRs) that give rise to hybrid FHR proteins also have been described in a few C3G patients but not in IC-MPGN patients. In this study, we used multiplex ligation-dependent probe amplification (MLPA) to study the genomic architecture of the CFH-CFHR region and characterise CNVs in a large cohort of patients with C3G (n=103) and IC-MPGN (n=96) compared to healthy controls (n=100). We identified new/rare CNVs resulting in structural variants (SVs) in 5 C3G and 2 IC-MPGN patients. Using long-read single molecule real-time sequencing (SMRT), we detected the breakpoints of three SVs. The identified SVs included: 1) a deletion of the entire CFH in one patient with IC-MPGN; 2) an increased number of CFHR4 copies in one IC-MPGN and three C3G patients; 3) a deletion from CFHR3-intron3 to CFHR3-3'UTR (CFHR34-6∆) that results in a FHR3-FHR1 hybrid protein in a C3G patient; and 4) a CFHR31-5-CFHR410 hybrid gene in a C3G patient. This work highlights the contribution of CFH-CFHR CNVs to the pathogenesis of both C3G and IC-MPGN.